Perancangan Mebel Multifungsi Untuk Fasilitas Display di Toko Power Tools & Bahan Bangunan Paku Waja Sidoarjo - Jessica Crystalie Santoso (Intra, 2017)
In recent years, it is seen that the increase in the number of retail turnover in the business of power tools and building materials is growing rapidly, which is also supported by the growing number of human needs and desires of getting instant. In reality, there are still at least businessman retail stores, who realized that the role of interior design in retail store design and display facilities (storefront) is a very important role to be a major attraction for visitors. Therefore, there arises a sense realized display facilities in retail stores also has a crucial and responsible in attracting consumers to sign in and shop in a store. One way to attract the attention of consumers is a wide - range, ranging from attractive display facility, also adjust the layout of the product as well as the furniture in the store. As a basic, the design process will begin by finding the background of the problem, look for the formulation of the problem, making the goal of designing, analyzing field data and observations, and  continued in later stages of the design process concludes with prototypesThis design has 3 sets of selection for some categories of products, namely, products power tools, pumps, and building materials. Construction systems that applied to this product is a multifunctional system and folding system that will focus on the function and aesthetics in its use. In addition, this product can also be easily moved and used for some commercial purposes such as exhibitions or particular event.